Application of Bakri's Balloon to postpartum obstetric hemorrhage. Case Presentation - Yoan Hernàndez Cabrera; Jorge Luis Diaz Puebla; Ana Beatriz Abreus Castro; Marioly Ruiz Hernandez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Obstetric hemorrhage after delivery complicates 10.5% of births worldwide and is related to high perinatal morbidity and mortality. Its management includes medical treatment and if refractory, it will be necessary to resort to a surgical treatment based on uterine tamponade with gauze or balloon, uterine compression sutures, pelvic devascularization and arterial embolization. If all these procedures are not effective, then a radical treatment such as obstetric hysterectomy should be performed. The case of a 37.5 week, nulliparous pregnant woman, attended at the Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos is presented. Labor is induced due to premature rupture of membranes that evolves into the active phase and it is decided to perform instrumental delivery by forceps to shorten the expulsive period by non-physiological variety and alteration of fetal well-being. A female 4025 g weight newborn was obtained, with greater obstetric hemorrhage due to uterine atony, which does not resolve with conventional medical treatment and it was decided to perform conservative management of the uterus by means of Barki´s balloon uterine compression. Uterine contractility and a satisfactory clinical evolution are achieved. This surgical procedure was first described worldwide by the end of the 20th century and was introduced in Cuba in 2016. Since then, the Cienfuegos province has implemented these conservative practices. In the case presented it was possible to reduce bleeding. In addition it reduces obstetric morbidity and mortality and preserves fertility in the patient with unmet parity